Best Practices and Innovations for Managing Codeine Misuse and Dependence - Norman, Ian J.; Bergin, Michael; Parry, Charles D.; Van Hout, Marie Claire (Journal of Pharmacy & Pharmaceutical Sciences, 2016)
Purpose. Promoting and ensuring safe use of codeine containing medicines remains a public health issue given the rise in reporting of misuse and dependence particularly in countries where available over–the-counter (OTC). The aim of this unique study was to identify best practices in management of opioid abuse and dependence, particularly codeine, and innovations to meet challenges surrounding safe and compliant use, patient awareness-raising, reducing health harms and enhancing successful treatment of dependence. Methods. A mixed methods approach using three data points was used that included : (1) analysis of data from existing scoping reviews to identify potential areas for innovation (2) interviews with key national stakeholders from public health, pharmaceutical, regulatory, primary care and addiction practice in three distinct regulatory regimes (Ireland, United Kingdom and South Africa); and (3) a circular email request for information on potential innovations to members of the European Medicine’s Agency European Network of Centres for Pharmacoepidemiology and Pharmacovigilance (ENCEPP). Data from these three sources were analysed to identify best practices and opportunities for innovation. Results. Best practices and potential innovations were identified under the nine headings: (1) manufacture; (2) product information and public education; (3) responsible prescribing; (4) monitoring and surveillance; (5) dispensing, screening and brief interventions in community pharmacies; (6) safety in the workplace and on the road; (7) internet supply of codeine and online support; (8) treatment of codeine dependence; and (9) learning resources and training for health professionals. Conclusions. Challenges ensuring availability of codeine containing medicines for legitimate therapeutic use, while minimising misuse, dependence and related health harms warrant consideration of new innovations. Most promising innovative potential lies across the products’ retail lifecycle from manufacture to prescriber and community pharmacy practitioner. This article is open to POST-PUBLICATION REVIEW. Registered readers (see “For Readers”) may comment by clicking on ABSTRACT on the issue’s contents page.